2009
DOI: 10.1002/jso.21339
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open gastrectomy for gastric cancer patients with COPD

Abstract: LG can be performed safely for patients with gastric cancer and COPD in stage I and II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Likewise, in most nonrandomized, comparative series, laparoscopic gastric cancer surgery was comparable to open surgery with respect to both short-and long-term results. [45][46][47][48][49][50][51][52][53] In several nonrandomized studies, one should be aware of a significant difference in disease stage between the laparoscopic and open surgery group.…”
Section: Structure Indicatorsmentioning
confidence: 99%
“…Likewise, in most nonrandomized, comparative series, laparoscopic gastric cancer surgery was comparable to open surgery with respect to both short-and long-term results. [45][46][47][48][49][50][51][52][53] In several nonrandomized studies, one should be aware of a significant difference in disease stage between the laparoscopic and open surgery group.…”
Section: Structure Indicatorsmentioning
confidence: 99%
“…In colorectal surgery, laparoscopic colectomy is associated with a significantly lower risk of pneumonia than open colectomy [13]. Whether laparoscopic gastrectomy affects the incidence of PPCs remains a matter of debate, although it seems to be feasible even in patients with chronic obstructive pulmonary disease (COPD) [14,15]. We performed this retrospective cohort study to identify risk factors for PPCs after radical gastrectomy for gastric cancer, including both open and laparoscopic procedures.…”
mentioning
confidence: 99%
“…Also, a meta-analysis showed that postoperative lung function was improved in patients undergoing laparoscopic compared to open colorectal surgery, but PPCs did not differ between groups [81]. Even in COPD patients, it could not be demonstrated that laparoscopic vs. open gastrectomy reduced PPCs [82]. Taken together, those studies seem to suggest that PPCs may be reduced in higher-risk populations when surgery is performed under laparoscopic compared to an open approach, but definitive evidence is missing.…”
Section: Laparoscopic Vs Open Surgerymentioning
confidence: 97%